The family Thermoactinomycetaceae: an emerging microbial resource with high application value - Zhong, Mingmei; Sun, Zhenchun; Wei, Chunhui; Muhoza, Bertrand; Tian, Haojie; Liu, Maoqiang; Qiu, Shuyi; Li, Dounan (Frontiers in Microbiology, 2025)
In recent years, interest has increased in the use of microorganisms to obtain additional valuable resources for green and sustainable development. Preliminary functional analyses have indicated that members of the family Thermoactinomycetaceae have good application potential for the production of novel specific enzymes, high-value bioactive compounds, novel secondary metabolites and the promotion of efficient biomass conversion. Therefore, they can be considered a new class of microbial resources with potentially high value. However, the lack of culture and culture-independent techniques coupled with the uncertain taxonomic status of the family Thermoactinomycetaceae, has made exploring these potential applications challenging. This paper reviews the distribution characteristics and functional properties of the family Thermoactinomycetaceae, providing a detailed interpretation of the potential application value of this group and proposing a set of systematic resource development strategies based on a combination of culture-dependent and culture-independent strategies to exploit its potential for resource applications.